Suboptimal PID control method for an electro-hydraulic system - Dang, Xuan Ba; Kyoung Kwan Ahn (Journal of Technical Education Science, 2017)
This research proposes an advanced proportional-integral-derivative (PID) controller for position-tracking control problem of a pump-controlled Electro-Hydraulic System (EHS). Although conventional PID controller is a practically robust and easy-to-use method, it is difficult to maintain good control performance of such system which contains both high nonlinearities and unknown terms. The key idea of the proposed approach is thus developed from a combination of the conventional PID signal, a robust nonlinear compensator which is properly derived from the system model, and a suboptimal regulator. Effectiveness and feasibility of the designed controller have been successfully evaluated through theoretical proof and experimental results of fast response (0.3s) and excellent steady-state error (0mm).